2022
DOI: 10.3390/app12094549
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality Control Methods to Test Strengthening Technologies: A Multilevel Model of Acoustic Pulse Flow

Abstract: This article describes an approach that makes it possible to substantiate quality control criteria and methods to improve strengthening technologies. The approach was used to test the quality of products made using these technologies and analyze different strengthening methods applied to structural materials. In the experiment, samples of welded joints subjected to various types of strengthening were used that underwent acoustic emission (AE) testing. The results of quick evaluations produced by the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
0
0
2
Order By: Relevance
“…Technological problems. This group includes such problems as the lack of modern types of equipment and technologies at all stages of the production cycle [13,14,49,62], the high import dependence of oil and gas companies [32,43,63,64], the low level of state technological development as a whole [13,49,65,66], etc.…”
Section: Problems and Prospects For The Development Of Russian Oil An...mentioning
confidence: 99%
“…Technological problems. This group includes such problems as the lack of modern types of equipment and technologies at all stages of the production cycle [13,14,49,62], the high import dependence of oil and gas companies [32,43,63,64], the low level of state technological development as a whole [13,49,65,66], etc.…”
Section: Problems and Prospects For The Development Of Russian Oil An...mentioning
confidence: 99%
“…A premature failure analysis of the steel coils of tubular furnace in oil refinery was carried out after an oil leak occurred, which led to an explosion and therefore to an emergency stop for maintenance and replacement of the damaged coils [8]. The analysis showed that failure is mainly caused by corrosion [13].…”
Section: Premature Failure Analysismentioning
confidence: 99%
“…Стандартные данные, получаемые по традиционным для полимерного и композиционного материаловедения методикам прочностного исследования (одноосное деформирование), малоинформативны [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Способ, основанный на информационно-кинетическом подходе к диагностированию и многоуровневой модели потока импульсов акустической эмиссии [30,31] может оказаться лучше. Результаты таких исследований необходимы для понимания механизмов разрушения и упрочнения полимерных материалов, оптимизации возможностей их практического применения.…”
Section: Introductionunclassified
“…После этого образцы нагружали на растяжение при комнатной температуре на универсальной разрывной машине Zwick/ Roell Z100 с постоянной скоростью деформирования. Для регистрации сигналов АЭ использовали автоматизированную акустико-эмиссионную диагностическую систему СДАЕ 16(2) [30,31]. Результаты регистрации обрабатывали по многоуровневой модели потока импульсов АЭ.…”
Section: Introductionunclassified